Project Report on Testing of Two Stroke Engine with Alternative Fuel (Methyl Alcohol-Gasoline Blends) - ABU JACOB GEORGE, THOMAS K ARGHESE, MARTIN J PHILIP, KURUVILLA T MATHAI, GOPAKUMAR P T and GEEVURGHESE K M (1993)
INTERNAL GUIDE: BALASUNDRA RAO R, MVJCE
Keywords: Two Stroke Engine with Alternative Fuel